Physicochemical properties and immune-enhancing activity of graded polysaccharides from the peels of stem lettuce (Lactuca sativa) by cascade membrane technology - Zou, Xian-Guo; Cao, Yu-Qin; Li, Jing-Jing; Guan, Xiao-Qian; Cai, Ming; Sun, Pei-Long; Yang, Kai (Frontiers in Nutrition, 2022)
In this study, cascade membrane technology was applied to classify polysaccharides from the peels of stem lettuce (PPSLs), and three graded polysaccharides (PPSL100, PPSL10 and PPSL1) were obtained using ultrafiltration membranes of 100, 10 and 1 kDa in sequence. The physicochemical properties and immune-modulatory activity of three PPSLs fractions were analyzed and compared. Results showed that all three fractions have characteristic absorption peak of polysaccharides determined by FT-IR, and their monosaccharide composition only consisted of glucose determined by HPLC. PPSL10 had the highest contents of total sugar (88.09% ± 3.52%), uronic acid (2.55% ± 0.10%) and sulfate group (4.15% ± 0.20%). Besides, all three fractions exhibited immune-enhancing activities using RAW264.7 macrophages model, and PPSL10 was the best able to promote phagocytosis of neutral red and nitric oxide generation, which might relate to the high contents of above compositions and medium molecular weight (32 kDa). The findings indicated that PPSL10 could be developed as immune-modulator in the field of functional foods.